LITHOLOGICAL DEDUCTIONS AND THE EVALUATION OF GROUNDWATER POTENTIALS FROM GEO-ELECTRICAL SOUNDINGS IN THE BENDE-AMEKI FORMATION OF EHIME-MBANO AREA, SOUTHERN NIGERIA - Amos-Uhegbu, Chukwunenyoke; Ndubueze, D. N.; Dinneya, O. C.; Aigba, P. I.; Akoma, C. D. (FUDMA Journal of Sciences, 2024)
Lithological deductions and evaluation of groundwater potentials from Geo-electrical soundings in the Bende-Ameki Formation of Ehime-Mbano Area, Southern Nigeria, was carried out by imploring the vertical electrical sounding (VES) technique. A total of nine VES points were obtained using the ABEM SAS 1000 Terrameter. The study reveals that the depth of the shallow wells in the area (upper aquifer) ranges from 12-22m and falls within the 3rd and 4th geo-electric layers with resistivity values ranging from 240m - 2500m; while the 2nd aquifer ranges from 34-45m and with range of resistivity values of 190m - 300m. The depth to the 3rd aquifer ranges from 70 120m, while that of the 4th aquifer is 130-300m. The data obtained after partial curve matching and computer iteration indicates a total of 8 - 10 geoelectric layers with inferred lithologies namely: silt, clay, fine-grained sand, medium-grained sand, coarse-grained sand and sandstone. Results show that most of the aquifers are hosted within the silts and fine-grained sands with the exception of a few locations with medium-grained and coarse-grained sands. By using the Dar-Zarrouk parameters, the overburden protective capacities of the aquifers in the study area were evaluated as poor, weak and moderate in some locations. It was concluded that in the area, sand mining (excavation) is a potential economic source except in the vicinity of VES 9.